Levodopa may affect cortical excitability in Parkinson's disease patients with cognitive deficits as revealed by reduced activity of cortical sources of resting state electroencephalographic rhythms - Babiloni, Claudio; del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Catania, Valentine; Nobili, Flavio; Arnaldi, Dario; Fama, Francesco; et al. (Elsevier Science Inc, 2019)
We hypothesized that dopamine neuromodulation might affect cortical excitability in Parkinson's disease (PD) patients set in quiet wakefulness, as revealed by resting state eyes-closed electroencephalographic (rsEEG) rhythms at alpha frequencies (8-12 Hz). Clinical and rsEEG rhythms in PD with dementia (N = 35), PD with mild cognitive impairment (N = 50), PD with normal cognition (N = 35), and normal (N = 50) older adults were available from an international archive. Cortical rsEEG sources were estimated by exact low-resolution brain electromagnetic tomography. Compared with the normal older group, the PD groups showed reduced occipital alpha sources and increased widespread delta (<4 Hz) sources. Widespread frontal and temporal alpha sources exhibited an increase in PD with dementia compared with PD with mild cognitive impairment and PD with normal cognition groups, as function of dopamine depletion severity, typically greater in the former than the latter groups. A daily dose of levodopa induced a widespread reduction in cortical delta and alpha sources in a subgroup of 13 PD patients under standard chronic dopaminergic regimen. In PD patients in quiet wakefulness, alpha cortical source activations may reflect an excitatory effect of dopamine neuromodulation.
WOS: 000450412900002
PubMed ID: 30312790
Keywords: Functional Brain Connectivity; Resting State EEG Rhythms; Mild Cognitive Impairment Due To Alzheimer's Disease (ADMCI); Mild Cognitive Impairment Due To Parkinson's Disease (PDMCI)